2002
DOI: 10.1128/jcm.40.12.4675-4678.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Commercial Assays with Expert Microscopy for Confirmation of Symptomatically Diagnosed Malaria

Abstract: Conventional light microscopy has been the established method for malaria diagnosis. However, recently several nonmicroscopic rapid diagnostic tests have been developed for situations in which reliable microscopy may not be available. This study was conducted to evaluate the diagnostic performance of a recently introduced ICT Malaria Pf/Pv test. This assay detects Plasmodium falciparum histidine-rich protein 2 antigen (PfHRP-2) for P. falciparum diagnosis and pan-malarial antigen for P. vivax diagnosis. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
71
3
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 26 publications
11
71
3
5
Order By: Relevance
“…In a study in Kuwait, Iqbal et al found 96% sensitivity when parasitemia was >500 parasites/µL and 44% sensitivity when parasitemia was <500 parasites/µL. 7 Kakkilaya in 2003 observed that many studies showed >95% sensitivity when parasitemia was 500 parasites/µL. 13 From the above discussion it is observed that some results are consistent with our findings and some remarkably differ from the present study.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In a study in Kuwait, Iqbal et al found 96% sensitivity when parasitemia was >500 parasites/µL and 44% sensitivity when parasitemia was <500 parasites/µL. 7 Kakkilaya in 2003 observed that many studies showed >95% sensitivity when parasitemia was 500 parasites/µL. 13 From the above discussion it is observed that some results are consistent with our findings and some remarkably differ from the present study.…”
Section: Resultssupporting
confidence: 82%
“…Among all the methods, microscopic examination of blood film is regarded as the 'gold standard'. 6,7 This method is relatively simple and cost-effective. But it is time consuming, needs expert microscopist and sensitivity is questionable at low level of parasitemia.…”
mentioning
confidence: 99%
“…Özellikle ataklar sırasında bakıldığında gerek kalın, gerekse ince yayma preparatlarında etkeni görme şansı oldukça yüksektir. [11] Bizim olgumuzda sıtmayı düşündüren hastanın ateşinin seyri ve seyahat öyküsüydü. Periferik yayma ve kalın damla incelemesi ile sıtma tanısını konuldu.…”
Section: Discussionunclassified
“…However, these methods rely on detection of antigens derived from the parasites, rather than detecting the parasites themselves. Though RDTs are often able to differentiate most malarial species by means of their antigenic properties, overall sensitivity of detection is far below the threshold of microscopy-based malaria detection, exhibiting huge variations among the patients [11][12][13][14][15] and failing to guide treatments which could be fatal when mixed infections occur [16]. These are efficient methods; however the results can vary depending on the severity of infection and the high occurrence of young parasitic forms (ringstage infections) in the peripheral blood, which are only beginning to establish metabolic processes.…”
Section: Introductionmentioning
confidence: 99%